Sensitive Interviewing in Qualitative Research. Issue 6 (19th July 2016) - Dempsey, Laura; Dowling, Maura; Larkin, Philip; Murphy, Kathy
Abstract: In this paper we focus on important considerations when planning and conducting qualitative interviews on sensitive topics. Drawing on experiences of conducting interviews with dementia caregivers, a framework of essential elements in qualitative interviewing was developed to emphasize study participants' needs while also providing guidance for researchers. Starting with a definition of sensitive research, the framework includes preparing for interviews, interacting with gatekeepers of vulnerable groups, planning for interview timing, and location, building relationships and conducting therapeutic interactions, protecting ethically vulnerable participants, and planning for disengagement. This framework has the potential to improve the effectiveness of sensitive interviewing with vulnerable groups. © 2016 Wiley Periodicals, Inc.